Pressure overload-induced mild cardiac hypertrophy reduces left ventricular transmural differences in mitochondrial respiratory chain activity and increases oxidative stress - KINDO, Michel; GERELLI, Sebastien; BOUITBIR, Jamal; CHARLES, Anne-Laure; ZOLL, Joffrey; HOANG MINH, Tam; MONASSIER, Laurent; FAVRET, Fabrice; PIQUARD, Francois; GENY, Bernard (Frontiers in Physiology, 2012)
Objective: Increased mechanical stress and contractility characterizes normal left ventricular subendocardium (Endo) but whether Endo mitochondrial respiratory chain complex activities is reduced as compared to subepicardium (Epi) and whether pressure overload-induced left ventricular hypertrophy (LVH) might modulate transmural gradients through increased reactive oxygen species (ROS) production is unknown. Methods: LVH was induced by 6 weeks abdominal aortic banding and cardiac structure and function were determined with echocardiography and catheterization in sham-operated and LVH rats (n=10 for each group). Mitochondrial respiration rates, coupling, content and ROS production were measured in LV Endo and Epi, using saponin-permeabilised fibres, Amplex Red fluorescence and citrate synthase activity. Results: In sham, a transmural respiratory gradient was observed with decreases in endo maximal oxidative capacity (-36.7%, P<0.01) and complex IV activity (-57.4%, P<0.05). Mitochondrial hydrogen peroxide (H2O2) production was similar in both LV layers. Aortic banding induced mild LVH (+31.7% LV mass), associated with normal LV fractional shortening and end diastolic pressure. LVH reduced maximal oxidative capacity (-23.6 and -33.3%), increased mitochondrial H2O2 production (+86.9 and +73.1%), free radical leak (+27.2% and +36.3%) and citrate synthase activity (+27.2% and +36.3%) in Endo and Epi, respectively. Transmural mitochondrial respiratory chain complex IV activity was reduced in LVH (-57.4 vs –12.2%; P=0.02). Conclusions: Endo mitochondrial respiratory chain complexes activities are reduced compared to LV Epi. Mild LVH impairs mitochondrial oxidative capacity, increases oxidative stress and reduces transmural complex IV activity. Further studies will be helpful to determine whether reduced LV transmural gradient in mitochondrial respiration might be a new marker of a transition from uncomplicated toward complicated LVH.